Facile Synthesis of Liquid Crystal Dimers Bridged with a Phosphonic Group. Issue 70 (2nd November 2022) - Wang, Dalin; Liu, Jiang; Zhao, Weiguang; Zeng, Yongming; Huang, Jianjia; Fang, Jianglin; Chen, Dongzhong
Abstract: Liquid crystal (LC) dimers with well‐defined composition and structure arouse broad attentions for their exhibiting LC properties beyond conventional low molar mass mesogens and serving as fascinating model compounds for LC polymers. Here in this work, a series of LC dimers bridged with a phosphonic group have been synthesized through a facile free radical mediated addition reaction between hypophosphorous acid and vinyl terminated cyanobiphenyl mesogens with variant length alkyl spacers. In addition, two esterified derivatives and a group of mono‐addition homologues with a terminal phosphonic acid group have also been prepared for comparison study. All the newly synthesized compounds exhibit monotropic nematic (N) phase with typical schlieren textures except for the LC dimer with the longest eleven‐methylene spacer, which surprisingly shows twist‐bend nematic (NTB ) phase directly from the isotropic state upon cooling. Moreover, the thermal transition properties such as the nematic‐isotropic transition temperatures and associated entropy changes of the series LC dimers display a modest odd‐even effect. Furthermore, both the LC dimers and the mono‐addition homologues in N phase are quite easy to achieve homeotropic alignment upon annealing thanks to the supramolecular interactions between the introduced phosphonic acid group and the hydroxylated glass surface. This work thus provides a novel synthesis strategy for a class of LC materials bridged with a phosphonic acid group prone to further functionalization, which may serve as promising vertical alignment agents and pave the way for developing a new kind of functionalized LC materials of NTB phase. Abstract : We report a novel synthesis strategy for facile access to a huge family of liquid crystal dimers or mono‐addition homologues characterized with phosphonic group, which is readily achieved with P−C bonding through addition reaction between P−H and non‐conjugated vinyl group. The introduced phosphonic group enables homeotropic alignment and further functionalization and one of the LC dimers exhibits NTB phase directly from the isotropic state.